Kecerdasan Buatan Sebagai Alat Bantu Proses Penyusunan Undang-Undang Dalam Upaya Menghadapi Revolusi Industri 4.0 di Indonesia - Paulus Wisnu Yudoprakoso (Simbur Cahaya, 2018)
Indonesia is a constitutional state is regulated in Article 1 verse (3) of the 1945 Constitution of the Republic of Indonesia. Its logical consequence is that every Indonesian citizen must submit to and obey the applicable law, legislation in this case. In its development, the law is expected to be constantly able to answer change and challenge of the people in changing time. Law is expected to always accommodate people to find the answers. It is in line with the Industrial Revolution 4.0 which currently happens. In this case, Artificial Intelligence is intended to support the forecasting and ranking on the matters which might require legislation in the future